2011
DOI: 10.1111/j.1551-2916.2011.04695.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Dielectric Properties of Bi (Mg1/2Ti1/2)O3–BaTiO3 Lead‐Free Ceramics

Abstract: By the conventional mixed oxide method (1Àx)Bi(Mg 1/2 Ti 1/2 ) O 3 -xBaTiO 3 ((1Àx)BMT-xBT, x = 0.2À1.0) ceramics were prepared. For x 0.4, a bismuth-rich phase was observed beside the perovskite phase. For 0.5x 0.92 ceramics, all the compositions belong to the pseudocubic phase, while the tetragonal phases were formed when x ! 0.94. With the increase of BT content, a change from a relaxor-like behavior to a normal ferroelectric behavior was observed, while the change of T max is in the form of "U" curve. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
60
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(70 citation statements)
references
References 23 publications
10
60
0
Order By: Relevance
“…A plot of r-T for the (1-x)BT-xBMT composition x = 0.5BMT fabricated in our laboratory is shown in Figure 3, values of r mid= 2100 ±15 % extended from 150-400ºC, in general agreement with literature data [23], but r is slightly lower than published values, possibly due to differences in ceramic density. Values of tan were ≤ 0.02 (100 KHz) from 270 to 550ºC, and ≤ 0.02 at 1 kHz for the narrow temperatures range 230-300ºC.…”
Section: Batio3-bi(mg05ti05)o3supporting
confidence: 70%
See 1 more Smart Citation
“…A plot of r-T for the (1-x)BT-xBMT composition x = 0.5BMT fabricated in our laboratory is shown in Figure 3, values of r mid= 2100 ±15 % extended from 150-400ºC, in general agreement with literature data [23], but r is slightly lower than published values, possibly due to differences in ceramic density. Values of tan were ≤ 0.02 (100 KHz) from 270 to 550ºC, and ≤ 0.02 at 1 kHz for the narrow temperatures range 230-300ºC.…”
Section: Batio3-bi(mg05ti05)o3supporting
confidence: 70%
“…Zhang et al, provided a detailed account of the temperature stability of dielectric properties [23]. Compositions x = 0.5BMT and 0.6BMT displayed a plateau in r-T response: for x = 0.5, values of r ~ 2400 ±15 % (1 kHz) were observed for temperatures 167 to 400ºC, with tan < 0.02 (100 kHz) for temperatures 238-400ºC.…”
Section: Batio3-bi(mg05ti05)o3mentioning
confidence: 99%
“…An alternative and low-cost system, (1-x)Ba 0.8 Ca 0.2 TiO 3 -xBi(Mg 0.5 Ti 0.5 )O 3 has r = 830 ± 10 % and low, tan ≤ 0.02, from ~50ºC to 550 ºC for composition x = 0.5; r = 950 ± 10 % over the wide temperature range from +80 °C to 600 °C for composition x = 0.45 [6,12,28]. The end member Bi(Mg 0.5 Ti 0.5 )O 3 is of rhombohedral structure at room temperature, with T c ~ 430 ºC but can only be prepared at high pressure (6 GPa) at a temperature ~1000 ºC [20,21]. However, it forms useful solid solutions under normal processing conditions with a number of other perovskites [6,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The low temperature dependence of the dielectric properties for the pseudocubic phase is in good agreement with previous reports for sintered bodies formed using BaTiO 3 -BiMO 3 solid solutions. [13][14][15][16][17][18][19] This is considered to be related to the relaxed behavior of these solid solutions, and the diffused temperature dependence of ε r , which reduces the overall temperature dependence of ε r . 20 In contrast, Mitsui et al reported that the maximum ε r was observed at more than 400 • C for x = 0.60.…”
Section: Methodsmentioning
confidence: 99%
“…11,12 Also, a low ε r temperature dependence has been reported for solid solution systems of BaTiO 3 and Bi-based perovskite oxides with pseudocubic structures at room temperature. Sintered bodies of BaTiO 3 -BiMO 3 [where M = Sc 3+ , Al 3+ , (Mg 0.5 Ti 0.5 ) 3+ , and (Zn 0.5 Ti 0.5 ) 3+ ] with pseudocubic symmetry show particularly high ε r stability at temperatures up to 400 • C. [13][14][15][16][17][18][19] In a previous study, we investigated the dielectric properties of ternary BaTiO 3 -Bi(Mg 0.5 Ti 0.5 )O 3 -BiFeO 3 solid solution films prepared by chemical solution deposition (CSD) as alternatives to BaTiO 3 -based high-ε r materials. 20 This system has a wide compositional region with a pseudocubic symmetry between the tetragonal and rhombohedral symmetries at room temperature.…”
Section: Introductionmentioning
confidence: 99%